The use of econometric models by Federal regulatory agencies - Steele, Joe L. (Lexington, Mass. : Heath Lexington Books, 1971)
This book examines the suitability of econometric models as primary tools of analysis for use by federal regulatory agencies.
Bibliography: p. 93-96.
rpm 20/02/2018
Loans
Keywords: Natural gas; Econometrics